Promotion strategy in increasing the tourists’ interest in visiting UPT Balanga Museum Palangka Raya City - Ariani, Angela; Hundjeh, Madia Putriana; Mulyantari, Enny (Technium Social Sciences Journal, 2022)
In this research, the writer chose ‘Promotion Strategy in Increasing the Tourists’ Interest in Visiting UPT Balanga Museum Palangka Raya City’ as the title of the research. This research was aimed to observe the promotion strategy which can be done by the museum manager in order to increase the tourists’ interest in visiting the museum. This research is qualitative descriptive research. Purposive sampling method was applied in collecting the data. There were six people which are: a manager and five tourists. The data collecting process of the research was also supported by observation and documentation. Furthermore, source triangulation technique was applied in order to observe its validity and reliability test. The data analysis was done by using SWOT analysis. The result of the research shows that UPT Balanga Museum needs to be repaired and it also needs to have promotion strategy improvement based on the 8 promotion mix. There were four promotion methods chosen as a focus in repairing the promoting strategy and used as UPT Balanga Museum intensely, which were advertising, event and experience, online marketing, and social media. The rest of the methods which are sales promotion, direct marketing, mobile marketing, and personal marketing are never be chosen as the focus of UPT Balanga Museum. It is because the tourists’ data was not complete enough. After doing this research, the writer concludes that UPT Balanga Museum has cooperated with print media (Kalteng Pos) and online media (@infokalteng). Moreover, UPT Balanga Museum is also collaborating with several schools and universities around Palangka Raya City. This museum also has its own Instagram and YouTube account as the promotion media.